Multigenetic pharmacogenomics–guided treatment shows greater improvements on motor symptoms compared to usual therapy in Parkinson’s disease: a small real-word prospective cohort study - Li, Yifan; Li, Mao; Wang, Miao; Yao, Jiarui; Li, Fengzhu; Chen, Siyu; Yin, Xi; Gao, Zhongbao (Frontiers in pharmacology, 2025)
Dopamine replacement therapy is a cornerstone of Parkinson's disease treatment. In clinical practice, there is considerable variability in patients' responses, tolerability, and safety regarding anti-parkinsonian medications, which is largely influenced by genetic polymorphisms in pharmacokinetic and pharmacodynamic genes. However, the application of multigenetic pharmacogenomics-guided treatment (MPGT) to optimize therapeutic outcomes in Parkinson's disease (PD) remains under-explored. In this study, we conducted a prospective cohort investigation to evaluate the potential benefits of MPGT on motor symptoms in PD patients. A total of 28 patients with PD were followed for 4 weeks. Among them, 22 patients underwent multigenetic pharmacogenomic testing, with 13 receiving treatments based on the test results (MPGT group). The remaining 15 received standard care (TAU group). Baseline characteristics, as well as changes in Unified Parkinson's Disease Rating Scale (UPDRS) III scores and sub-scores, were compared between the two groups. Associations between various single nucleotide polymorphisms (SNPs) and treatment outcomes were analyzed using generalized linear models. At the 4-week follow-up, the MPGT group showed significantly greater reductions in UPDRS III total scores (p < 0.05) and limb sub-scores (p < 0.01) compared to the TAU group. These differences remained significant after adjusting for increases in levodopa equivalent daily dose ( 0.011 and 0.002, respectively) and piribedil use ( 0.006 and 0.004, respectively). Patients homozygous for the major allele of rs4984241 (AA vs. AG+GG, 0.003), rs4680 (GG vs. GA+AA, 0.013), rs1076560/rs2283265 (CC vs. AC+AA, 0.039) and rs622342 (AA vs. AC, 0.043) showed greater improvement in total UPDRS III, postural instability and gait difficulty (PIGD), rigidity and tremor scores, respectively, compared to those carrying at least one minor allele. MGPT demonstrates significant potential as a valuable tool for personalized treatment in PD patients. Additionally, we identified several SNPs associated with the responsiveness to chronic administration of multiple anti-parkinsonian drugs. However, to confirm these findings, well-designed studies with larger, well-characterized samples are necessary.